Air Oxidation of Carbon Spheres. I. Master Curves of Pore Parameters - Tetsuo Nishikawa; Michio Inagaki (Adsorption Science & Technology)
Carbon spheres prepared from a resol-type phenol–formaldehyde resin at 1000°C were activated in a flow of dry air in order to understand the process of pore development through the use of master curves for each pore parameter. Pore development in the carbon spheres by such oxidation was characterized through analyses of nitrogen adsorption isotherms by different methods. The adsorptivity of the activated carbon spheres towards phenol was measured as a function of oxidation temperature and time, its dependence on the micropore volume being discussed. The development of pores by air oxidation was interpreted in terms of master curves measured at the reference temperature (400°C) for each pore parameter, viz. surface areas and pore volumes due to different pores. The pore parameters were determined via the BET, α S -plot, BJH and DFT methods. The results presented suggest that the effect of oxidation temperature and time on pore development could be converted with each other as well as oxidation yield. The temperature dependence of the different parameters corresponded to an apparent activation energy of ca. 150 kJ/mol. Pore development was assumed to proceed principally via the enlargement and collapse of micropores through mesopores to macropores.